Trends in STEM education from 2020 to 2023: A critical review in selected academic publications - Wahidin, Naufal Rabah; Rochintaniawati, Diana; Agustin, Rika Rafikah (Universitas Islam Negeri Imam Bonjol Padang, 2024)
The numerous amounts of research regarding STEM education in the last five years indicate that every country put their eyes on the development of STEM education itself. In the school settings, the STEM education rises starting from middle school to higher education. There is a need in reviewing the articles of STEM education for middle school students. By selecting 17 articles indexed by Scopus and has a grade of Q1, this study was conducted. The results of this critical review shows that the majority of articles can be divided into big three themes; the integration of STEM education with other instructional approaches, STEM and gender, and professional development in STEM education. This study implies that various instructional approaches can maximized STEM education to foster students learning output. There is also no correlation between gender and their cognitive skills while learning STEM subject. The most important thing, STEM education can be more successful if the teachers got a proper professional development.